Validity Analysis of Electronic Student Worksheets Based on Guided Inquiry to Improve Students' Critical Thinking Skills - Wulandahri Wulandahri; Hidayati Hidayati; Yenni Darvina; Fuja Novitra (Jurnal Penelitian Pembelajaran Fisika, 2025)
This research was motivated by the fact that the teaching materials used in physics learning are still largely dominated by conventional textbooks, teacher’s books, and Student Worksheets (SWS). The aim of this study is to develop guided inquiry-based Student Worksheets that can enhance students' critical thinking skills in the topics of temperature and heat. The developed Student Worksheets are expected to be not only valid in terms of content and structure but also effective in facilitating a more meaningful learning experience for students. This study employs a Research and Development (R&D) approach. The validation process was carried out by three physics lecturers from the State University of Padang (UNP). The analysis of the validation instrument results showed that the developed Student Worksheets obtained a validation score of 0.95, which falls into the "very valid" category. Therefore, the product developed in this study a guided inquiry-based Student Worksheet is considered valid and suitable for use as an innovative teaching material to improve students' critical thinking skills in understanding the concepts of temperature and heat.